Reliability and Validity of a New Method for Isometric Back Extensor Strength Evaluation Using A Hand-Held Dynamometer - Park, Hee-won (Ann Rehabil Med, 2017)
OBJECTIVE: To investigate the reliability and validity of a new method for isometric back extensor strength measurement using a portable dynamometer. METHODS: A chair equipped with a small portable dynamometer was designed (Power Track II Commander Muscle Tester). A total of 15 men (mean age, 34.8±7.5 years) and 15 women (mean age, 33.1±5.5 years) with no current back problems or previous history of back surgery were recruited. Subjects were asked to push the back of the chair while seated, and their isometric back extensor strength was measured by the portable dynamometer. Test-retest reliability was assessed with intraclass correlation coefficient (ICC). For the validity assessment, isometric back extensor strength of all subjects was measured by a widely used physical performance evaluation instrument, BTE PrimusRS system. The limit of agreement (LoA) from the Bland-Altman plot was evaluated between two methods. RESULTS: The test-retest reliability was excellent (ICC=0.82; 95% confidence interval, 0.65–0.91). The Bland-Altman plots demonstrated acceptable agreement between the two methods: the lower 95% LoA was −63.1 N and the upper 95% LoA was 61.1 N. CONCLUSION: This study shows that isometric back extensor strength measurement using a portable dynamometer has good reliability and validity.